Evaluating the diagnostic accuracy of TpN17 and TmpA recombinant proteins in syphilis detection: a phase II study - Silva, Ângelo Antônio Oliveira; Lima, Ayla Araújo; Vasconcelos, Larissa Carvalho Medrado; Almeida, Rosângela Andrade; Freitas, Natália Erdens Maron; Oliva, Talita Andrade; de Carvalho Ribeiro da Silva, Miralba Freire; Marchini, Fabricio Klerynton; Zanchin, Nilson Ivo Tonin; de Siqueira, Isadora Cristina; Santos, Fred Luciano Neves (Frontiers in Microbiology, 2024)
Syphilis is a sexually transmitted infection (STI) caused by the spiral bacterium Treponema pallidum.Diagnosis is based on epidemiology, clinical and serology, but serodiagnosis is challenging because distinct clinical forms of the infection may influence serological performance. Several recombinant Treponema pallidum-proteins have already been tested for syphilis diagnosis and they are critical to achieve high accuracy in serological testing. Our aim was to assess the performance of treponemal recombinant proteins (TpN17 and TmpA) for the detection of anti-T. pallidum in syphilis-positive individuals. A total of 647 samples were included in the study: 180 T. pallidum-positive samples, 191 T. pallidum-negative samples and 276 sera from individuals infected with unrelated diseases. The diagnostic potential was validated by analysis of ROC curves. For the indirect ELISA, TpN17 (100%) and TmpA (99%) showed excellent AUC values. Sensitivity values were 97.2% for TpN17 and 90.6% for TmpA, while specificity was 100% for both molecules. According to the clinical phase, TmpA ranged from 84% to 97%, with the highest value for secondary syphilis. TpN17 was 100% sensitive for the primary and secondary stages and 93.2% for recent latent syphilis. All clinical phases achieved 100% specificity. Accuracy values showed that TmpA (> 95%) and TpN17 (> 98%) presented high diagnostic accuracy for all clinical stages of syphilis. Cross-reactivity was only observed in one sample positive for Chagas disease (1.5%), when TpN17 was evaluated. On the other hand, TmpA showed reactivity for two samples positive for Chagas disease (3.1%), one sample positive for HBV (1.25%), two samples positive for HIV (9.5%) and one sample positive for HTLV (1.6%). According to the diagnostic parameters evaluated, the proteins showed high diagnostic performance in diagnosing syphilis regardless of the clinical stage of the disease.